OPHTHALMOMYASIS (OCULAR MYASIS) - Muhammad Marwat (Gomal Journal of Medical Sciences, 2014)
The invasion of human organs and tissues by the larvae of the order Diptera is called myiasis. There are more than 85,000 Diptera species. However few of them involve ocular tissues. Ophthalmomyiasis is the involvement of ocular tissues by these larvae, more often due to the sheep nasal bot fly (Oestrus ovis Linnaeus) or human bot fly (Dermatobia hominis Linnaeus). Ocular involvement is seen in 5% of all cases of myiasis. Keyt was the first who described a case of ophthalmomyiasis in 1900.